2022
DOI: 10.3390/ijms23042103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxidative Stress-Induced Apoptosis on Active FGF23 Levels in MLO-Y4 Cells: The Protective Role of 17-β-Estradiol

Abstract: The discovery that osteocytes secrete phosphaturic fibroblast growth factor 23 (FGF23) has defined bone as an endocrine organ. However, the autocrine and paracrine functions of FGF23 are still unknown. The present study focuses on the cellular and molecular mechanisms involved in the complex control of FGF23 production and local bone remodeling functions. FGF23 was assayed using ELISA kit in the presence or absence of 17β–estradiol in starved MLO-Y4 osteocytes. In these cells, a relationship between oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 83 publications
(141 reference statements)
1
11
0
Order By: Relevance
“…Numerous signaling pathways are involved in the osteoblast process, containing the Wnt/β-catenin, ERK1/2, and phosphatidylinositide-3 kinase (PI3K)/Akt pathways. 33 In previous studies, we had found that C3G promotes the proliferation of MC3T3-E1 without Wnt/β-catenin. 15 In this study, it was illustrated that the signaling pathways ERK1/2 had some relationships with C3G's capacity for inducing osteoblast differentiation.…”
Section: ■ Discussionmentioning
confidence: 93%
“…Numerous signaling pathways are involved in the osteoblast process, containing the Wnt/β-catenin, ERK1/2, and phosphatidylinositide-3 kinase (PI3K)/Akt pathways. 33 In previous studies, we had found that C3G promotes the proliferation of MC3T3-E1 without Wnt/β-catenin. 15 In this study, it was illustrated that the signaling pathways ERK1/2 had some relationships with C3G's capacity for inducing osteoblast differentiation.…”
Section: ■ Discussionmentioning
confidence: 93%
“…Postmenopausal osteoporosis is also related to enhanced osteocyte senescence and apoptosis [ 90 , 91 , 92 , 93 ]. Indeed, the activation of MAPK signaling due to oxidative stress mediates the increase in apoptosis, RANKL/OPG ratio, sclerostin, and FGF23 levels, and the decrease in autophagy in osteocytic MLO-Y4 cells [ 28 , 94 , 95 ]. In these cells, the high levels of glucose increase ROS production and apoptosis through the downregulation of the AMP-activated protein kinase (AMPK)/FOXO3a signaling pathway [ 96 ].…”
Section: Oxidative Stress and Osteoporosis: Principal Involved Molecu...mentioning
confidence: 99%
“…All this can contribute to the activity of bone cells and thereby bone homeostasis by increasing and inhibiting osteoclastic and osteoblastic function [ 23 ]. Indeed, both oxidative stress and inflammation can be involved in the development of osteoporosis by preventing the differentiation of osteoblasts, inducing the differentiation and activity of osteoclasts, enhancing apoptotic osteocytes, and increasing the expression of RANKL and the RANKL/OPG-ratio [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several potential mechanisms may explain the association between FlOPs and QUS parameters. Numerous lines of evidence suggest that oxidative stress is involved in the process of bone remodeling, inducing an imbalance between osteoclastic bone resorption and osteoblastic bone formation (7,38,39). Excessive ROS affects the differentiation and activity of osteoclasts by regulating mitogen-activated protein kinases (MAPKs), nuclear factor-kappa (NF-κB), and Ca 2+ -mediated signaling cascades (40).…”
Section: Discussionmentioning
confidence: 99%